(untitled) (Interdisciplinary Studies Journal, 2024)
This work presents the analysis of a qualitative research with participatory research methodology, which aimed to develop educational activities related to health with Basic Education students. The research problem is: How to guide prevention regarding risk behaviors involving health issues with Basic Education students? The activities contained in a pedagogical booklet were applied and developed with students from a State School located in the Rural Zone of the State of RS. The data was produced from audio recordings, logbook records and reports. This manuscript discusses and analyzes the activities of the pedagogical issue. The data obtained highlighted the importance of addressing issues related to health, risk behaviors and quality of life with students, thus showing that school can be a suitable place to address these issues.